Privacy matching-based service proxy discovery scheme - Kui GENG; Sheng WAN; Feng-hua LI; Yuan-yuan HE; Han-yi WANG (Tongxin xuebao)
According to user's requirements on the proxy performance,cost and safety in proxy discovery,and the pri-vacy-preserving issue during the process of the demand private matching,a new private matching algorithm was pre-sented based on Paillier homomorphic encryption,comprehensively considered the attributes of user and agents and their priority.It included four steps:building the similarity function based on Euclidean distance,carrying on the private matching by encryption algorithm,calculating the similarity and screening the proxy chain.Proposed scheme introduced semi trusted primary proxy from the global level,which is to manage all the sub proxy's business type and the connection status,and do the main computational overhead.At the same time,Euclidean distance and Paillier homomorphic encryp-tion algorithm were combined to support the multivariate attributes with priority to match,which can effectively protect the privacy of user and sub proxy.Finally,security analysis and evaluation results show the effectiveness and safety of proposed scheme.